Integration of Ibn Khaldun's Thought in Contemporary Social Analysis, Perspectives of Islamic Sociology - Surni Kadir (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This article aims to analyze the relevance of Ibn Khaldun's thought, specifically through his work Muqaddimah, in explaining contemporary social dynamics from the perspective of Islamic sociology. Ibn Khaldun is known as one of the early Islamic thinkers who developed unique social concepts, such as asabiyyah (group solidarity) and civilizational cycles, which became the foundation for the social analysis of society. This study uses a qualitative analysis method with a descriptive-analytical approach to trace the integration of Ibn Khaldun's theories into the context of modern social issues, including social change, poverty, and the sustainability of civilization in the era of globalization. Through this study, it was found that Ibn Khaldun's thought is still very relevant in understanding the dynamics of social groups and the factors that affect the collapse or revival of a society. The concept of asabiyyah, for example, can be applied in analyzing community solidarity in the face of global challenges, while the cycle of civilization offers a critical perspective on sustainable development. This article concludes that the integration of Ibn Khaldun's thought into contemporary Islamic sociology is able to provide a deep theoretical framework for understanding social change in modern society, as well as enriching the approach of Islamic sociology in facing the realities of the times.